(untitled) (Health Renaissance, 2012)
Acute monoarthritis can be the initial manifestation of many joint disorders. The first step in diagnosis is to verify that the source of pain is the joint, not the surrounding soft tissues. The most common causes of monoarthritis are crystals (i.e., gout and pseudo gout), trauma, and infection. Here, we present a case of 24-year-old young lady who had presented to the Orthopaedic depatment of B.P.Koirala Institute of Health Sciences, Dharan, Nepal with pain,swelling and restriction of movement of right elbow for 3 days. With all these characteristics and literature reviewed, we thought that this case unique and rare and needs to be reported. Health Renaissance; September-December 2012; Vol 10 (No.3);244-250 DOI: http://dx.doi.org/10.3126/hren.v10i3.7056